RANCANG BANGUN MESIN PENDETEKSI NOMINAL UANG RUPIAH KERTAS DENGAN OUTPUT SUARA DAN PENUKAR UANG RUPIAH UNTUK TUNA NETRA BERBASIS MIKROKONTROLLER - Yultrisna Yultrisna; Rahmat Rahmat; Muhammad Aidil (Situs resmi ITP Press, 2016)
How to make a system that fungtion for give a simple tuna netra for know have money and people in change moneys with microcontroller. Microcontroller can control color sensor for detected color in money, and give some RGB in serial monitor. Some date in serial monitor devide 3 condition is R, G and B. Color sensor is used to TCS3200-DB, have some fungtion for R output, G output and B output. For see output RGB must turn off condition R, G and B. How to the process sound money can be ISD2500 module and have IC (Integrated Circuit) ISD2500. IC ISD2500 have many IC, it is ISD 25120 (for 120 second record ), ISD 2590 (for 90 second record) and ISD 2560 (for 60 second record) mechine can give information about how to use the machine about fungtion box, fungtion button and nominal out money. Know the money using color sensor for input, microcontroller for process and sound for output. If the money Rp 100.000 inside to box in, so output say “Seratus Ribu Rupiah”. If the money Rp 50.000 inside to the box in, so output say “Lima Puluh Ribu ” and if the money Rp 10.000 inside to the box in, so output say “Sepuluh Ribu Rupiah”.3 condition using between money Rp 100.000, Rp 50.000 and Rp 20.000. and change with Rp 10.000. how many maney to out in box change same with how much the money change